COMPLAINT BEHAVIOR: RELATIONSHIPS INDIVIDUALISM, SELF CONFIDENCE AND VOICE INTENTION WITH GENDER AS MODERATING VARIABLE - Sri Hartini; Aventina Aventina (STIE Perbanas Surabaya, 2013)
The study aims to explain the customers complaint behavior. This especially attempts to revealthe relationships among antecedent variables ofcomplaint behavior. The study uses hypothetically quantitative design research toexplain relationships among variables. Due to the infinitenumber of population, accidental sampling technique is implemented. Path analysis and subgroup analysis were adopted to analyze the data. It was found that that customers individualismaffect customers self confidence and gender was found tobe a moderating variable in the relationships. The customers self confidence influences the customers voice intention and genderwas not moderating in this relationships. The customers individualism did not affect the voiceintention and gender was found to be the moderating variable inthis relationship.